The Effectiveness of Flashcard Media in Improving Javanese Vocabulary Among Kindergarten A Students - Dwi Bhakti Indri; Ajeng Vika Faradina; Hany Aulia (Chalim Journal of Teaching and Learning, 2025)
This study is motivated by the low level of students’ ability to recognize Javanese vocabulary, mainly due to the lack of appropriate learning materials. To address this issue, flashcards were used to stimulate students’ interest and improve their recognition of Javanese vocabulary. This research employed a Classroom Action Research (CAR) design to improve Javanese vocabulary mastery among Kindergarten-A students using flashcards. The problem arose from monotonous, less varied learning conditions that were still dominated by lecture methods and unengaging instructional media. The study focused on two variables: Javanese vocabulary mastery as the dependent variable and the use of flashcards as the independent variable. The population comprised all 15 Kindergarten-A students at TK Nuruddinul Islam, selected through purposive sampling. The findings indicate an improvement in students’ vocabulary skills following the implementation of flashcards. In the pre-cycle stage, most students (60%) were classified as Fair, whereas the remainder were classified as Poor or Very Poor. In Cycle I, all students showed progress and reached the Fair category, with no students remaining in the lower categories. More significant progress was observed in Cycle II, in which six students (40%) achieved the Good category, and only one student continued to demonstrate limited ability. These results demonstrate that flashcards are effective learning aids for enhancing Javanese vocabulary mastery among Kindergarten-A students.